Sison amomum L. (Apiaceae), a new species in the flora of Bosnia and Herzegovina - Maslo, Semir (Array, 2020)
Sison amomum L. (Apiaceae) was recorded for the first time in Bosnia and Herzegovina during a fieldwork in the vicinity of the city of Tuzla (northeast Bosnia) in September 2019. This study reports the newly discovered localities and presents a short morphological description of the species.